Training Branding and Merchandising Products to Support the Marketing Strategy of the Furniture Industry in Jepara - Kristianto, Fesa Putra; Broto, Taukhid Wisnu; Ma'rifah, Juli Dewi; Puspitaningsih, Fitri Indah; Sabila, Maharsi Anis (Jurnal Pengabdian Masyarakat, 2024)
The furniture industry provides a fairly high foreign exchange where the industry is labor-intensive with a high export value. During 2022, its export value reached 3.5 billion USD and 1.3% of Indonesia's total export performance in 2022. However, this value fell by 8.04% from last year due to the Russian-Ukrainian war and the global economic downturn. Therefore, to support marketing strategies and improve export performance, the Furniture Industry Business Management (MBIF) study program conducts branding and merchandising training. This community service activity (PKM) is carried out in the form of lectures and practices. The material presented in the form of basic furniture for the development of small and medium industries, branding concepts, branding strategies, digital marketing and merchandising Practices. For evaluation using pre-test, post-test and the results of branding or merchandising uploaded on social media. This training is expected to improve the understanding of branding and merchandising and implement it into its export marketing strategy. So that the export performance of the furniture industry in Jepara can rise in 2023.